Perancangan Sistem Informasi Berbasis Web Pada IT CONNECTS - Sigit Birowo (Jurnal Informatika dan Bisnis, 2013)
At this modern era, any corporation who wants to develop and survive in the business competition must have the ability to maintain a good relationship with the customer-to-be dan the existing customers. So, IT Connects decided to build an e-Commerce to support the business, so they could develop and compete with any similar corporates. The objective of this research is to design a website to market and sell the products on-line. The website consists of two sides, the front side (front end) and back side (back end). Front end (web pages) is designed and written in programming language, which is HTML and PHP using Macromedia Dreamweaver 8 website editor. Back end uses MySQL to design the databases with the tables that are already normalizationized. Connectsion to database server using XAMPP. Collecting information and user needs through interviews to the owner of the IT Connects store. Designed system is presented with data flow diagrams and entity relationship diagrams. The data dictionary is used as a source of data for the process of normalization to create the data into tables in the database. The IT Connects website has several advantages, which are there is a shopping cart, the ability to make an order and corfirm payments on-line, the ability to see testimonials, provide ratings on each item purchased. And the owner will be presented reports which are sales report, top product report, top customer report, dan top rated product report.The conclusions from this research are that the website could help IT Connects to do the selling process on-line, make the marketing dan information spreading of IT Connects easier, dan the ability to provide reports that are useful to the owner.